(untitled) (Ukrainian Journal of Ophthalmology, 2026)
We analyzed the incidence and prevalence of selected nosologies of eye diseases. The analysis was conducted among the adult population of Sumy region within 2005 - 2015 years. We observed a reduction in primary incidence by 4.26%, against the background of unstable prevalence rates. Thus, the latter was reduced by 8% from 2005 to 2010, and, afterwards, it rapidly returned to 2005 rates. The first, second and third places in the distribution of the newly diagnosed eye diseases among Sumy region adults took conjunctival diseases, cataract, and keratitis and scleral diseases, respectively.